Mathematical Thinking Styles Among Engineering Students: Perceptions Versus Assessment Test - Nadrah, Wan Hanim; Ab Halim, Fazlinda; Lai, Chee sern; Syed Abdullah, Syed Shahrul Zarizi (Journal of Technical Education and Training, 2019)
Algebra is regarded as one of the primary learning domains as it represents the fundamental entry knowledge to higher forms of learning in  mathematics, science, technology and engineering. The acquisition of Algebraic knowledge depends greatly on learnersâ€™ Mathematical Thinking Style (MTS). Therefore,  this study  aimed  to investigate the  university studentsâ€™ MTS  through the algebraic problem-solving topic.  In general, the MTS was composed of analytical, visual, and integrated thinking styles. In this research,  mixed method research design was adopted in which  questionnaire  and assessment test were used for data collection. A total of 248  engineering students in Universiti Tun Hussein Onn Malaysia were involved in the data collection process. Descriptive statistics  was used to analyse the quantitative data obtained from the questionnaire, whereas the written answers from the assessment test were analysed using  document analysis technique.  The findings indicated that majority of the participating students perceived that they commonly practiced  the Analytical Thinking Style in learning Algebra. However, analysis on the studentsâ€™ problem solving steps in the assessment test revealed that the students were actually applying Visual Thinking Style in Algebraic problem solving tasks instead of Analytical Thinking Style. This study revealed that there was a difference  between studentsâ€™ perception and the analysis outcomes from the assessment test which reflected the actual MTS of the students. This difference reflects the fact that how an individual perceives his behaviour might not be consistent with his actual behaviour. In conclusion, instructors should know the actual MTS of the students instead of finding out studentsâ€™ perception on their thinking style. This will help instructors design more relevant learning activities that beneficial to students.